The Relationship between Family History and C-peptide Level in Type2 Diabetic Patients - Abed, Baydaa A. (Journal of the Faculty of Medicine Baghdad, 2013)
Background: Family history of type 2 diabetes is a major risk factor for type 2 diabetes. Type 2 diabetes is characterized by progressive β-cell dysfunction; many investigators have used C peptide levels as a biomarker of β-cell function.Objective: the current study was design to investigate the impact of family history on biochemical characteristics (c-peptide, HbA1c, lipid profile, insulin secretion, insulin sensitivity and insulin resistance.J Fac Med Baghdad2013; Vol.55, No .3Received Feb .2013Accepted July.2013Subjects and methods: three hundreds patients (152 males 148 females) with type 2 DM were enrolled in this study; and two hundreds individual serves as a control groups (103 male 97 female). The following clinical characteristics were reported: age, sex, waist circumference WC, systolic blood pressure SBP, diastolic blood pressure DBP, family history, body mass index BMI, laboratory analyses included serum c-peptide, blood glycosylated hemoglobin (HbA1c) assay, lipid profile which included serum cholesterol, serum triglyceride(TG), serum low density lipoprotein cholesterol (LDL) and serum high density lipoprotein-cholesterol (HDL). Insulin secretion, sensitivity and resistance were calculated from fasting serum glucose (FSG) (mg/dl) and C-peptide (ng/ml) values by homeostasis model assessment (HOMA).The statistical analysis was done by SPSS (statistical packagefor social sciences- version 17).Result: Statistically was observed that highly significant increase in serum C-peptide in patients compared to control group (3.85±1.02 vs 1.53±0.24 p